2016
DOI: 10.1177/1751143716662055
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic liver disease on the intensive care unit – Outcomes and prognostication

Abstract: These results are similar to previous studies with no significant improvement in outcomes. Alcoholic liver disease is not a contra-indication to intensive care unit admission but assessment of the individual patient is required. The most appropriate objective factors to guide prognostication are the presenting intensive care unit diagnosis and Sequential Organ Failure Assessment score. First presentation of alcoholic liver disease is not a positive prognostic indicator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…26 Physiological based scoring systems have a greater discriminatory capacity to predict outcome compared to liver-specific scores in patients with DLD. 13,14,22,27 SOFA performed the best with area under the curve (AUC) values of 0.86 in this study, comparative to other studies which calculated an AUC >0.90. 7,13,28 SOFA outperformed MELD-Na (AUROC: 0.71) in this study which has demonstrated previously to be the most useful of the liver-specific scores for this patient group.…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations
“…26 Physiological based scoring systems have a greater discriminatory capacity to predict outcome compared to liver-specific scores in patients with DLD. 13,14,22,27 SOFA performed the best with area under the curve (AUC) values of 0.86 in this study, comparative to other studies which calculated an AUC >0.90. 7,13,28 SOFA outperformed MELD-Na (AUROC: 0.71) in this study which has demonstrated previously to be the most useful of the liver-specific scores for this patient group.…”
Section: Discussionmentioning
confidence: 40%
“…Physiological based scoring systems have a greater discriminatory capacity to predict outcome compared to liver‐specific scores in patients with DLD . SOFA performed the best with area under the curve (AUC) values of 0.86 in this study, comparative to other studies which calculated an AUC >0.90 .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Christensen et al reported that up to 7.3% of patients entering ICUs in Denmark were alcoholics [16]. It should be noted that only 25% of these patients were defined as having “complicated” alcohol dependency syndrome [17].…”
Section: Discussionmentioning
confidence: 99%